Retail Management and Analysis of Consumer Behaviour of Youth in Mumbai: A Case Study on Shoppers Stop - Vaja, Reshma A. (SFIMAR Research Review, 2017)
Retailing came down from the West and spread over almost all countries of the world. Technological changes and E-commerce made the retail business more organized. Kind of shopping that people undertake has changed. In a busy world people are constrained by time and patience. Easy and quick availability of everything at one place is what they look out for. This attitude kills their worries, saves time and energy. This study focuses on aspects of retail management and consumer behaviour at one of the departmental retail mall, the Shoppers Stop. Study gives brief overview of behaviour/buying pattern of youth toward shopping malls.